PELAKSANAAN BUNKER MT CROWN FORTUNE DI PERAIRAN SINGAPORE - Herdiga, Fauzi (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
Sea transportation is currently developing very rapidly, ships as a means of sea transportation play an important role in smooth, safe and appropriate transportation Ships carrying liquid cargo are generally referred to as tankers, several types of tanker cargo are premium, diesel, Pertamax, aftermarket kerosene, fuel oil, gas oil. For this reason, handling cargo on tankers really requires expertise, accuracy and good cooperation from the entire ship's crew. Method is descriptive and qualitative, researcher use observation, interview as well documentation (triangulation) in data collection. Researcher collect data at once test data validity with do interview with sources, method This used for analyze causative factors can’t be optimal security payload containers The results of this research are the implementation of MT CrownFortune Bunker in Singapore waters which aims to avoid incidents during the implementation of Bunker in Singapore waters. The implementation of Bunker on the MT Crown Fortune ship has several obstacles, including a lack of understanding by the crew regarding the procedures for carrying out Bunker, a lack of coordination between crew members before the Bunker begins, a lack of communication between the crew members of the MT Crown Fortune and the crew members of the ship that is being bunkered. Handling incident prevention during Bunker is by familiarizing yourself with Bunker procedures and holding a safety meeting before carrying out Bunker.